HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI PASIEN HIPERTENSI DALAM MENGONTROL TEKANAN DARAH DI PUSKESMAS SIMPANG TIGA - Nur Hasanah; Yulia Rizka; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Hypertension is a non-communicable disease and is one of the most important contributors to heart disease and stroke which together are the number one cause of premature death and disability in the world. Hypertension control can be done if the patient regularly checks blood pressure at a health facility. Blood pressure control cannot be separated from one's motivation. This study aims to determine the relationship between family support and the motivation of hypertensive patients to control their blood pressure. The design of this   research is the descriptive correlation with the cross-sectional approach. The population in this study were hypertensive patients at the Simpang Tiga Public Health Center. The sampling technique in this study used purposive sampling with a total sample of 66 respondents. The data collection technique used a family support questionnaire and a control motivation questionnaire which contained 22 valid and reliable statements data analysis using a chi-square test. The showed that 43 respondents (65.2%) had high support and 58 respondents (87.9%) had high motivation. Based on the results of the chi-square test, p-value = 0.115 (>0.05). There is no relationship between family support and the motivation of hypertensive patients to control blood pressure at the Simpang Tiga Health Center.Keywords: Blood pressure control; family support; hypertension; motivation.